1986
DOI: 10.1021/jo00373a021
|View full text |Cite
|
Sign up to set email alerts
|

Further kinetic evidence for the competitive rotational and inversional Z-E isomerization of substituted azobenzenes

Abstract: Supplementary Material Available: Description of the X-ray diffraction determination of 3, including final atomic positional parameters (Tables 3 and 4), thermal parameters (Table 5), and selected bond distances and bond angles (Table 6), (6 pages); observed and calculated structure factors (Table 7) (12 pages). Ordering information is given on any current masthead page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 1 publication
1
57
1
Order By: Relevance
“…The rates are also solvent dependent, with many derivatives exhibiting an increase in thermal rate with increasing polarity, 16,30,36,37,42 although sometimes the opposite behaviour is observed. 43,44 Thermal rates are enhanced at low pH where protonation at the azo moiety reduces the activation barrier. 16,[45][46][47] The dipolar character of the thermal transition state is proposed to be similar to that of the excited state.…”
Section: Modifying Photoswitching Wavelengths and Thermal Relaxation mentioning
confidence: 99%
“…The rates are also solvent dependent, with many derivatives exhibiting an increase in thermal rate with increasing polarity, 16,30,36,37,42 although sometimes the opposite behaviour is observed. 43,44 Thermal rates are enhanced at low pH where protonation at the azo moiety reduces the activation barrier. 16,[45][46][47] The dipolar character of the thermal transition state is proposed to be similar to that of the excited state.…”
Section: Modifying Photoswitching Wavelengths and Thermal Relaxation mentioning
confidence: 99%
“…This can be attributed to the poor solubility of the azobenzene block due to the protonation of carboxylic group in acid condition, which leads to inter/intra-molecular hydrogen bond and further induces tightly aggregated particles. Obviously, the inter/intra-molecular hydrogen bond of azo carboxylic acid is too strong to be destroyed by UV light irradiation [51,52]. In this case, the photoisomerization of azobenzene moieties can hardly take place due to this tight aggregate state, which provides relatively stable fluorescence intensity in acid condition.…”
Section: Fluorescence Property Influenced By Uv Irradiationmentioning
confidence: 99%
“…Asano et al reported two different routes of thermal Z to E isomerization: inversion and rotation [31,32]. The inversion route proceeds through a linear transition state in which one of the nitrogen atoms is sp hybridized, whereas the rotation route involves a TS where the electrons of p bond are delocalized over the entire molecule and so the rotation around the remaining s bond is allowed.…”
Section: Z-e Thermal Relaxationmentioning
confidence: 99%